2017
DOI: 10.1038/s41551-017-0131-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed imaging for diagnosis and therapy

Abstract: Complex molecular and metabolic phenotypes depict cancers as a constellation of different diseases with common themes. Precision imaging of such phenotypes requires flexible and tuneable modalities capable of identifying phenotypic fingerprints by using a restricted number of parameters whilst ensuring sensitivity to dynamic biological regulation. Common phenotypes can be detected by in vivo imaging technologies, and effectively define the emerging standards for disease classification and patient stratificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
102
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(106 citation statements)
references
References 226 publications
(265 reference statements)
0
102
0
1
Order By: Relevance
“…Such acquisitions reinforce antibody-based imaging approaches by enabling simultaneous interrogation of multiple antigens, as well as the combined interrogation of antigen status together with assessment of anatomic, metabolic or microenvironmental signatures. [68][69][70] In a classic example of simultaneous dual-isotope SPECT, Kelty et al demonstrated potential enhancement of metastatic lesion detectability in prostate cancer with [ 111 In]In-capromab pendetide (ProstaScint®), when ugmented with an anatomic (vascular) signature via 99m Tc-labeled RBCs in a 40-patient clinical trial. 71 Currently the clinical relevance of SPECT remains upheld due to its pivotal use as a theranostic tool, especially in dosimetric monitoring in RIT.…”
Section: Spectmentioning
confidence: 99%
See 1 more Smart Citation
“…Such acquisitions reinforce antibody-based imaging approaches by enabling simultaneous interrogation of multiple antigens, as well as the combined interrogation of antigen status together with assessment of anatomic, metabolic or microenvironmental signatures. [68][69][70] In a classic example of simultaneous dual-isotope SPECT, Kelty et al demonstrated potential enhancement of metastatic lesion detectability in prostate cancer with [ 111 In]In-capromab pendetide (ProstaScint®), when ugmented with an anatomic (vascular) signature via 99m Tc-labeled RBCs in a 40-patient clinical trial. 71 Currently the clinical relevance of SPECT remains upheld due to its pivotal use as a theranostic tool, especially in dosimetric monitoring in RIT.…”
Section: Spectmentioning
confidence: 99%
“…In contrast to PET, CLI favors high-energy beta-emitting radionuclides, eg, 18 F < 89 Zr < 124 I < 68 Ga < 90 Y. 74,75 Namely, the advantages afforded by high energy beta emitters stems primarily from 2 factors: (1) a greater energy differential with respect to the Cerenkov emission threshold produces more photons along the beta trajectory (ie, higher photon intensity), and (2) increased range of the beta particle results in a greater fraction of imageable photons created near the tissue surface where photon attenuation is decreased.…”
Section: CLImentioning
confidence: 99%
“…Conventional cancer treatment methods, including surgery, chemotherapy, radiotherapy, photothermal therapy, and immunotherapy, often lead to treatment failure due to tumor complexity, diversity, and heterogeneity 1 . Multimodal diagnostic and therapeutic agents (theranostics) based on cooperative enhancement between two or more treatments are expected to achieve synergistic therapeutic effects and real-time monitoring of treatment efficacy [2][3][4] . Clinically, comprehensive imaging and therapeutic strategies have been shown to enhance the therapeutic effects for cancer patients 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…As compared to conventional NIR fluorescence imaging in the first NIR window (NIR‐I) (700–900 nm), fluorescence imaging in the second NIR window (NIR‐II) (1000–1700 nm) exhibits salient advantages of deeper penetration and higher spatiotemporal resolution, owing to further reduced photon scattering, absorption, and tissue autofluorescence in biological tissues . Another strategy to overcome the drawbacks of conventional imaging modalities is to use multimodal imaging integrated with two or more modalities, which takes advantages of respective strength and compensates for inherent shortcomings of each modality, leading to increased imaging accuracy . Therefore, NIR‐II fluorescence and multimodal imaging hold great promise in efficient brain‐tumor diagnosis.…”
mentioning
confidence: 99%